Assistance In The Use Of Multimedia In Learning As An Effort To Improve The Skills And Skills Of Elementary School Teachers - Suchyadi, Yudhie; Indriani, Rini Indriani Sri; Anwar, Wawan Syahiril; Sudarjat, Jaja; Santa, Santa; Mirawati, Mira; Muhajang, Tatang; Yusup, Muthia Khairunnisa Putri (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Increasing competitiveness in the field of education, especially basic education, must continue to be carried out and. The challenges of education in the educational era 4.0 are very big, especially in increasing the nation's competitiveness. Teachers generally have a universal educational background. This service activity was carried out in the form of Assistance in the Use of Multimedia in Learning at Nurul Iman Islamic Elementary School. This activity aims to provide solutions to partner schools as a learning medium. In this activity, the participants consisted of 20 teachers. This service activity also aims to increase teacher competence in strengthening technology. This activity is very useful for teachers to support their professionalism in their work. Teachers need to be trained and guided so that they have skills in technological resources, which are based on education and teaching. The benefits obtained by teachers are improving the quality of research-based learning and increasing skills in mastering technology in learning. The implementation of this activity was carried out in two stages, namely training and guidance on learning media-based technology. The results are expected to show that teachers at Nurul Iman Islamic Elementary School, Parung District will understand how to utilize technology in learning media to improve the quality of learning and share information and experiences.